2016
DOI: 10.1104/pp.16.00136
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Visualization of the Dynamics in Xylem Embolism Formation and Removal in the Absence of Root Pressure: A Study on Excised Grapevine Stems  

Abstract: 95618 (A.J.M.) Gas embolisms formed during drought can disrupt long-distance water transport through plant xylem vessels, but some species have the ability to remove these blockages. Despite evidence suggesting that embolism removal is linked to the presence of vessel-associated parenchyma, the underlying mechanism remains controversial and is thought to involve positive pressure generated by roots. Here, we used in situ x-ray microtomography on excised grapevine stems to determine if embolism removal is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 53 publications
3
84
0
1
Order By: Relevance
“…This result implies that the lumen surface is neither completely hydrophilic (i.e., zero contact angle) nor completely hydrophobic (contact angle >90°). Previous observation of contact angles between water and lumen surfaces of xylem conduits range from 40 to 90° with the most commonly observed values between 40 and 55° (Schneider et al, 2000;Zwieniecki and Holbrook, 2000;van Ieperen et al, 2001;Brodersen et al, 2010;Kim and Lee, 2010;Lee et al, 2013;McCully et al, 2014;Knipfer et al, 2016). Purified lignin has a contact angle somewhere between 46 and 56° (Notley and Norgren, 2010).…”
Section: Possible Functional Implications Of the Findingsmentioning
confidence: 98%
See 2 more Smart Citations
“…This result implies that the lumen surface is neither completely hydrophilic (i.e., zero contact angle) nor completely hydrophobic (contact angle >90°). Previous observation of contact angles between water and lumen surfaces of xylem conduits range from 40 to 90° with the most commonly observed values between 40 and 55° (Schneider et al, 2000;Zwieniecki and Holbrook, 2000;van Ieperen et al, 2001;Brodersen et al, 2010;Kim and Lee, 2010;Lee et al, 2013;McCully et al, 2014;Knipfer et al, 2016). Purified lignin has a contact angle somewhere between 46 and 56° (Notley and Norgren, 2010).…”
Section: Possible Functional Implications Of the Findingsmentioning
confidence: 98%
“…In recent years, a growing number of studies have found that xylem surfaces tend to be somewhere between hydrophilic and hydrophobic, with observed aqueous contact angles ranging from about 40° to a little more than 90° (Schneider et al, 2000;Zwieniecki and Holbrook, 2000;van Ieperen et al, 2001;Shen et al, 2008;Kohonen and Helland, 2009;Brodersen et al, 2010;Kim and Lee, 2010;Lee et al, 2013;McCully et al, 2014;Knipfer et al, 2016), where a contact angle of 0° denotes a completely hydrophilic surface and contact angles above 90° a hydrophobic one. Other recent studies have shown that xylem surfaces, at least in angiosperms, feature a complex spatial arrangement of surfaces with hydrophilic and hydrophobic properties (McCully et al, 2014;Schenk et al, 2017), including coatings consisting at least in part of amphiphilic lipids (Schenk et al, 2017).…”
Section: Invited Special Articlementioning
confidence: 99%
See 1 more Smart Citation
“…However, cavitation reversal, when it occurs at all, requires that xylem water potentials relax to at least a few bars below zero over a time scale of hours (Hochberg et al, 2016;Knipfer et al, 2016), conditions that may not be met diurnally. Reversible collapse would be as effective as cavitation in increasing the gain of an abscisic acid (ABA) signal mediated by mesophyll turgor (or cell volume) during a transient increase in E (Zabadal, 1974;Pierce and Raschke, 1980;McAdam and Brodribb, 2016), even as it protected upstream xylem.…”
Section: Sensitivity Of the Modelmentioning
confidence: 99%
“…Living cells are required for making new wood (in this issue : Jacobsen et al, 2018;Johnson et al, 2018), but they also play important roles in maintaining and repairing the water transport system by refilling embolized conduits (Knipfer et al, 2016) and possibly by ionic control of hydraulic conductance through wood (Nardini et al, 2011). Both these functions in angiosperms are provided by living cells that are in contact with vessels, sometimes surrounding them completely.…”
mentioning
confidence: 99%